Typical somatic symptoms of pregnancy and their impact on a diagnosis of major depressive disorder - Yonkers, Kimberly Ann; Smith, Megan V.; Gotman, Nathan; Belanger, Kathleen (General hospital psychiatry, 2009)
We sought to determine whether trimester of pregnancy influences the ability to diagnose major depressive disorder (MDD). Eight hundred thirty-eight subjects completed a Composite International Diagnostic Interview and the Edinburgh Postnatal Depression Scale (EPDS) before 17 weeks of pregnancy, at 26–30 weeks of pregnancy and at 4–12 weeks postpartum. Subjects responded to a checklist of MDD symptoms regardless of stem question endorsement. We compared rates of symptom expression by response (Y/N) to stem questions, and trimester, using logit analysis. Receiver operating characteristic curves determined optimal EPDS thresholds. Most symptoms from the DSM-IV checklist were endorsed significantly more often in the first compared to later trimesters (odds ratios ranged from 1.39 to 14.16 for the first vs. later trimesters), independent of response to depression stem questions or medication treatment. Despite this, stem-positive and stem-negative groups differed significantly for 10 out of 13 symptoms (odds ratios, 2.29–6.89), independent of trimester. The EPDS had an optimal cutoff of 10 and showed acceptable predictive value. Pregnant women commonly experience somatic and other symptoms in this first trimester, but depressed women still differ from those who are not depressed. “Appetite increase,” “oversleeping” and “increase in energy” (e.g., agitation) were uninformative with regard to an MDD diagnosis.